223k views
0 votes
Another One, twenty points, you will be reported if you answer incorrectly.

Another One, twenty points, you will be reported if you answer incorrectly.-example-1

1 Answer

0 votes

Step-by-step answer:

First, we need to understand the rule of exponents.

When powers of a particular variable are multiplied, the exponents add.

For example, x^3*x^4 = x^(3+4) = x^7 ......................(1)

When there is a division, the exponents subtract.

For example, y^5/y^3 = y^(5-3) = y^2 ....................(2)

Also, the distributive property says

p*(q+r+s) = pq + pr + ps ......................(3)

Using the above basic rules, we have

-a^2b^2c^2*( a + b - c )...................... use (3) to distribute

= -a^2b^2c^2*a -a^2b^2c^2*b + a^2b^2c^2*c..................use (1) to multiply

= -a^3b^2c^2 -a^2b^3c^2 + a^2b^2c^3

User Wallybh
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.